Фазова рівновага пара-рідина розчинів диметилтелуру та диметилкадмію - Герасимчук, С. І.; Полюжин, І. П.; Мельник, Г. В.; Павловський, Ю. П.; Сергеєв, В. В.; Gerasymchuk, S.; Poliuzhyn, I.; Melnyk, H.; Pavlovskyi, Yu.; Serheyev, V. (Lviv Politechnic Publishing House, 2020)
Для опису рівноваги пара–рідина в системі диметилтелур-диметилкадмій запропоновано напівемпіричну модель Вільсона. Параметри моделі Вільсона розраховано за допомогою методу ітерацій математичного пакету програм Mathсad 14 на основі даних, отриманих із вимірювання температурної залежності тиску насиченої пари високочистих зразків диметилтелуру, диметилкадмію та їхнього еквімолекулярного розчину. За параметрами моделі Вільсона розраховано коефіцієнти активності компонентів розчину, коефіцієнт розділення, надлишкові функції розчину (HE, GE, TSE) та побудовано ізотермічні Р-Х діаграми стану системи диметилтелур-диметилкадмій. За результатами розрахунків зроблено висновки: про існування асоціації молекул у системі диметилтелур-диметилкадмій в еквімолекулярному співвідношенні; про від’ємне відхилення цієї системи від закону Рауля; про гомогенність розчину диметилтелур-диметилкадмій в усьому інтервалі концентрацій та температур (280–340 К).

To describe the vapor-liquid equilibrium in the dimethyltelluride-dimethylcadmium system, we proposed a semiempirical Wilson model. The parameters of the Wilson model were calculated using the method of iterations by means of the Mathsad 14 software package based on the data obtained by us to measure the temperature dependence of the saturation vapor pressure for high-purity samples of dimethyltelluride, dimethyl cadmium and their equimolecular solution. For the parameters of the Wilson model, the activity coefficients of the solution components, the partition coefficient, the excess solution functions (HE, GE, TSE) were calculated, and isothermal P-X state diagrams for the dimethyltelluride-dimethyl cadmium system were ploted. Based on the results of the calculations, the following conclusions were reached: the existence of molecules association in equimolecular ratio for the dimethyltellurdimethylcadmium system; the negative deviation of this system from Raoul’s law; on the homogeneity of the dimethyltellur-dimethylcadmium solution over the entire concentration and temperature range (280–340 K).
Phase vapor–liquid equilibrium for the solutions of dimethyltelluride and dimethylcadmium
Keywords: диметилтелур; диметилкадмій; модель Вільсона; азеотроп; тиск насиченої пари; діаграма стану; коефіцієнти активності; надлишкові функції змішування; dimethyltelluride; dimethylcadmium; the Wilson model; azeotrope; saturated vapor pressure; status chart; activity coefficients; redundant blending functions